The chromosomal passenger complex (CPC) as a key orchestrator of orderly mitotic exit and cytokinesis - Kitagawa, Mayumi; Lee, Sang Hyun (Frontiers in Cell and Developmental Biology, 2015)
Understanding the molecular network of orderly mitotic exit to re-establish a functional interphase nucleus is critical because disordered mitotic exit inevitably leads to genomic instability. In contrast to the mechanisms of the entrance to mitosis, however, little is known about what controls the orderly exit from mitosis, particularly in mammalian cells. The chromosomal passenger complex (CPC), which is composed of Aurora B, INCENP, Borealin and Survivin, is one of the most widely studied and highly conserved hetero-tetrameric complexes. The CPC orchestrates proper chromosome segregation with cytokinesis by targeting to specific locations at different stages of mitosis. Recent studies reveal that controlling CPC localization and Aurora B kinase activity also serves as a key surveillance mechanism for the orderly mitotic exit. This ensures the reformation of a functional interphase nucleus from condensed mitotic chromosomes by delaying mitotic exit and cytokinetic processes in response to defects in chromosome segregation. In this review, we will summarize the latest insight into the molecular mechanisms that regulate CPC localization during mitotic exit and discuss how targeting Aurora B activity to different locations at different times impacts executing multiple mitotic exit events in order and recently proposed surveillance mechanisms. Finally, we briefly discuss the potential implication of deregulated Aurora B in inducing genomic damage and tumorigenesis with current efforts in targeting Aurora B activity for anti-cancer therapy.